Pola Asuh Demokratis dan Keterampilan Interpersonal Pada Fase Pertengahan Perkembangan Anak - Ernasiwi Astri Oktavilia; Arfi Nurul Hidayah (Universitas Ahmad Dahlan, 2022)
Democratic Parenting style and Interpersonal Skills In the Middle Phase of Child Development. This study aims to determine the effect of democratic parenting on children's interpersonal skills. Quantitative research methods used in this study, research instruments in the form of a scale, democratic parenting scale and interpersonal skills scale. Determination of the research sample using purposive random sampling technique with the final number of subjects 59 children aged 9-11 years. The results obtained R2=0.350 and a correlation coefficient of 0.000 (p <0.050) meaning that this research hypothesis is accepted, democratic parenting has a positive influence on interpersonal skills, the effective contribution of democratic parenting contributes 45.3% to children's interpersonal skills. The conclusion of this study has a positive influence between democratic parenting of parents on children's interpersonal skills. The subject's perception of democratic parenting is in the high category and the subject's interpersonal skills are in the medium category.